Resonance raman spectroscopy of nitric oxide reductase and cbb3 Heme-Copper oxidase - Pinakoulaki, Eftychia; Varotsis, Constantinos (My University, 2008)
Elucidating the structure and properties of the active sites in cbf 3 heme-copper oxidase and in nitric oxide reductase (Nor) is crucial in understanding the reaction mechanisms of oxygen and nitric oxide reduction by both enzymes. In the work here, we have applied resonance Raman (RR) spectroscopy to investigate the structure and properties of the binuclear heme b3-CuB center of cbb3 heme-copper oxidase from Pseudomonas stutzen and the dinuclear heme b3-FeB center of Nor from Paracoccus denitrificans in the ligand-free and CO-bound forms and in the reactions with O2 and NO. The RR data demonstrate that in the Nor/NO reaction, the formation of the N-N bond occurs with the His-Fe heme b3 bond intact, and reformation of the heme b3-O-Fe B dinuclear center causes the rupture of the proximal His-Fe heme b3 bond. In the reactions of Nor and cbb3 with O 2, distinct oxidized heme b3 species, which differ from the as-isolated oxidized forms, have been characterized. The activation and reduction of O2 and NO by cbb3 oxidase and nitric oxide reductase are compared and discussed
Keywords: Nitrogen oxides; Enzymes; Ligands; Oxidation; Raman spectroscopy; Resonance; Chemistry; Cytochrome oxidase; Oxygen